Porous Carbons Derived from Desiliconized Rice Husk Char and Their Applications as an Adsorbent in Multivalent Ions Recycling for Spent Battery. (27th May 2022) - Sun, Yating; Su, Geng; He, Zhaocai; Wei, Yuan; Hu, Jinbo; Liu, Huaifei; Liu, Gonggang
Abstract : Recycling of spent lithium-ion batteries (LIBs) has attracted increasing attentions recently on account of continuous growth demand for corresponding critical metals/materials and environmental requirement of solid waste disposal. In this work, rice husk as one of the most abundant renewable fuel materials in the world was used to prepare rice husk char (RC) and applied to recycle multivalent ions in waste water from hydrometallurgical technology dispose of spent LIBs. Rice husk char with specific surface area and abundant pores was obtained via pickling and desilication process (DPRC). The structural characterization of the obtained rice husk char and its adsorption capacity for multivalent ions in recycled batteries were studied. XRD, TEM, SEM, Raman, and BET were used for the characterization of the raw and the modified samples. The results show rice husk chars after desilication has more flourishing pore structure and larger pore size about 50–60 nm. Meanwhile, after desilication, the particle size of rice husk char decreased to 31.392 μ m, and the specific surface area is about 402.10 m 2 /g. Its nitrogen adsorption desorption curve (BET) conforms to the type IV adsorption isotherm with H3 hysteresis ring, indicating that the prepared rice husk char is a mesoporous material. And the adsorption capacity of optimized DPRC for Ni, Co, and Mn ions is 7.00 mg/g, 4.84 mg/g, and 2.67 mg/g, respectively. It also demonstrated a good fit in the Freundlich model for DPRC-600°C, and a possible adsorption mechanism is proposed. The study indicates biochar materials have great potential as an adsorbent to recover multivalent ions from spent batteries.